SISTEM INFORMASI PENJUALAN BERBASIS WEB (QR – CANTEEN) DI SMA NEGERI 2 MEDAN - Mei Hotma Mariati Munte (Jurnal Abdimas Bina Bangsa, 2023)
The existence of SMA Negeri 2 Medan canteen is becoming increasingly attractive to school residents because school canteens can also be used by students to sell sell foods and drinks to increase their money. This devotion uses waterfall method as a system development method that can be used by sellers who want to join in the canteen. The result of the devotion is to create an application named qr – canteen that will be implemented in school canteen and sorroundings. Also this apllication has won gold medal when participating at Kuala Lumpur even